Safety of antidepressants in adults aged under 65: protocol for a cohort study using a large primary care database - Coupland, Carol; Morriss, Richard; Arthur, Antony; Moore, Michael; Hill, Trevor; Hippisley-Cox, Julia (BioMed Central, 2013)
Background: Antidepressants are among the most commonly prescribed drugs in primary care in England and their use is increasing. This is largely due to longer durations of treatment of depression. Observational studies have shown some differences in adverse outcomes associated with different antidepressant drugs but relatively little is known about their relative safety particularly with long term use. The primary aim of this study is to determine the relative and absolute risks of pre-defined adverse events comparing different classes of antidepressant drugs in adults aged under 65 years and diagnosed with depression.